Early Complications of Suture Closure of Perforated Duodenal Ulcer: A Study of 100 Cases - Hannan, ABMA; Islam, B; Hussain, M; Haque, MM; Kudrat-E-Khuda, MI (TAJ: Journal of Teachers Association, 2009)
Perforated Duodenal Ulcer is one of the commonest surgical emergencies, most prevalent in middle aged male persons. Most perforations of doudenum are spontaneous but there is an increasing incidence of perforation following the use of NSAIDs. Repair of duodenal ulcer perforation is an urgent and contaminated operation. So, patients may develop post operative complications, like wound sepsis, pneumonia, paralytic ileus, septicemia, shock, electrolyte imbalance, repair failure, duodenal fistula, intra abdominal abscess, burst abdomen etc. Here 100 cases of Perforated Duodenal Ulcer was admitted in surgical wards of R.M.C.H from 01.01.2004-31.12.2005 and all of them underwent laparotomy suture closure of perforation and peritoneal toilet. Meticulous postoperative follow up was done for an average period of 7-10 days to see the complications. 21 post operative complications were found among 100 patients. Most complications occurred in elderly patients with delayed admission, I e, 48 hours after symptoms. The commonest complications were pulmonary (4%), pelvic collection (4%), wound infection (3%), septicemia (2%), burst abdomen (2%), paralytic ileus (2%). 2 out of the 100 cases died from post-operative septicemia. Better prognosis can be expected in young patients who come early with a stable haemodynamic state. doi: 10.3329/taj.v18i2.3192 TAJ 2005; 18(2): 122-126